2012 IEEE International Ultrasonics Symposium 2012
DOI: 10.1109/ultsym.2012.0030
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of tissue harmonic synthetic aperture imaging on a commercial ultrasound system

Abstract: This paper presents an imaging technique for synthetic aperture (SAI) tissue harmonic imaging (THI) on a commercial ultrasound system. Synthetic aperture sequential beamforming (SASB) is combined with a pulse inversion (PI) technique on a commercial BK 2202 UltraView system. An interleaved scan sequence that performs dynamic receive focused (DRF) imaging and SASB, both using PI, is implemented. From each acquisition four images can be created: DRF image, SASB image, tissue harmonic DRF image (DRF-THI), and tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…SASB can generate an acoustic field intense enough to create harmonics for THI, and it has been suggested that these techniques be combined to improve the image quality of SASB even further. The pulse inversion technique was used to generate THI, and the beamforming steps for the final SASB-THI image are illustrated in Figure 1 (Hemmsen et al 2014b;Rasmussen et al 2012;Yigang et al 2011). In a preliminary study in which healthy volunteers were scanned, two radiologists evaluated the image quality of SASB-THI as equal to that of a conventional imaging technique combined with THI (DRF-THI), indicating that SASB-THI can be used for medical imaging (Rasmussen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…SASB can generate an acoustic field intense enough to create harmonics for THI, and it has been suggested that these techniques be combined to improve the image quality of SASB even further. The pulse inversion technique was used to generate THI, and the beamforming steps for the final SASB-THI image are illustrated in Figure 1 (Hemmsen et al 2014b;Rasmussen et al 2012;Yigang et al 2011). In a preliminary study in which healthy volunteers were scanned, two radiologists evaluated the image quality of SASB-THI as equal to that of a conventional imaging technique combined with THI (DRF-THI), indicating that SASB-THI can be used for medical imaging (Rasmussen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of SASB, besides the reduction in computational load, is that the lateral resolution remains higher and more uniform over depth compared to regular dynamic receive focusing (DRF) 19 . The use of virtual sources in SASB has been shown to create an acoustic field intense enough to generate harmonics 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…The default imaging technique in many modern ultrasound scanners is the combination of Dynamic Received Focusing (DRF) and Tissue Harmonic Imaging (THI) [1]. Tissue harmonic imaging (THI) enhances image quality through improvement in contrast, resolution and fewer artifacts in gray scale ultrasonography [2][3].…”
mentioning
confidence: 99%
“…Then, the image data are beamformed using the fixed focus points as a virtual source to obtain the final synthetic aperture [4,[8][9]. SASB use of virtual sources creates an acoustic field intense enough to create harmonics for THI [1,9]. To attain the improvement of THI and SASB, this combination was suggested as a new imaging technique [1,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation